Plasma concentrations of pro-inflammatory cytokine IL-6 and anti-inflammatory cytokine IL-10 in short and long term opioid users with non-cancer pain - Mizher, Hussam A.; Zin, Che Suraya; Helal Uddin, A.B.M.; Mohamed, Abdul Hadi; Tan, Hung Ling; M. Izat, Munira (2019)
INTRODUCTION Little is known whether the duration of opioid use influences the concentrations of pro and anti-inflammatory cytokines. OBJECTIVES This study examined the plasma concentration of pro-inflammatory cytokine, IL-6, and anti-inflammatory cytokine, IL-10, in short, and long-term opioid users with non-cancer pain. METHOD Adult patients with opioid therapy for noncancer pain were recruited from pain clinics at two tertiary hospital settings in Malaysia between February 2016 and March 2017. They were stratified into short-or long-term users based on opioid prescriptions ≥ 90 days per year. A 10 ml blood sample was taken for the analysis of plasma concentrations of IL-6 and IL-10 and were quantified using a highly sensitive multiplex assay. RESULTS Of 38 patients recruited, 24% (n=9/38) and 76% (n=29/38) were respectively short and long-term opioid users. Short term use of opioid was associated with higher levels of IL-6 (mean ±SD, 173.9 ± 13.7 pg/ml) and IL-10 (50 ± 5.8 pg/ml), while long term use of opioids was associated with lower levels (no significant difference) of both cytokines (IL6 (125 ± 16.1 pg/ml) and IL10 (41.3 ± 6.7 pg/ml). There was strong correlation between IL-6 and IL-10 within the same group (r² = 0.72, p < 0.05) and (r² = 0.76, p<0.05) for short and long-term users, respectively. CONCLUSION The duration of opioid use may modulate the level of pro-inflammatory cytokines in which it was higher in short term use and lower in long term use, but the effect of pain relief was similar as both cytokines were well correlated.